Ethical leadership and organizational support for creativity at work - Esguerra, Gustavo A.; Jáuregui, Kety; Espinosa, Juan C. (Creativity Studies, 2022)
With permanents global changes, organizations are increasingly required to promote employee creative behavior to deal with competitiveness keeping ethical leadership practices and responsible models of management. The purpose of this research is to investigate the effect of ethical leadership on creativity and estimates the mediating effect of organizational support for creativity in this relationship. A cross-sectional approach with a sample of 258 professionals, employees of different companies and economic sectors in the city of Lima, Peru, was employed. Valid and reliable instruments were used to assess the perception of the variables studied, and direct and indirect effects were tested using structural equation models. The results indicate that ethical leadership positively influences creativity both directly and through organizational support for creativity. This draws attention to the opportunity that leaders have to optimize organizational processes, procedures, and protocols oriented toward responsibility and respect for others to encourage creative behavior in employees. Furthermore, theoretical, and practical implications are discussed.